Biotechnological potential of brewing industry by-products - Mussatto, Solange I. (2009)
The manufacture of beer inevitably involves generation of various residues and by-products. The most common by-products are spent grains, spent hops and surplus yeast, which are generated from the main raw materials used for beer elaboration, the barley malt, hop and yeast, respectively. These three brewery by-products are available in large quantities throughout the year, but their use has still been limited, being basically sold to local dairy farmers to be used as cattle feed, or simply as a land fill. However, they represent large potential resources for use in biotechnological processes, in consequence of their complex compositions containing carbon, nitrogen and minerals. Several attempts have been made to use them in biotechnological processes, as for example in fermentative processes for the production of value-added compounds (xylitol, arabitol, ethanol, lactic acid, among others); as substrate for microorganisms cultivation, or simply as raw material for extraction of compounds such as sugars, proteins, acids and antioxidants. From an environmental viewpoint, the elimination of industrial by-products represents a solution to pollution problems, and merits thus large attention. In this chapter, the main characteristics and potential applications of the three main brewery by-products are reviewed focusing on their use in biotechnological processes.